PENGARUH PELAYANAN KOPERASI SIMPAN PINJAM DALAM MENINGKATKAN PRODUKTIVITAS USAHA KECIL PASAR BECEK DI KABUPATEN TIGARAKSA PROPINSI BANTEN - Nurhadi Nurhadi (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2016)
The economy is structured as a joint venture based on the principle of kinship. with the globalization launched by the government following the signing of free trade, the fate of any co-faced with anxiety onslaught of foreign products. Like a "willing umbrella before it rains", then the cooperative as the cornerstone of Indonesia's economy should continue to be develop in Teru consisten  in order to meet ideals. Variables used include small business productivity variable (Y) service cooperatives (X1) savings and loans (X2) at the Tigaraksa.located at Tenjo Kingdom market tangerang warehouse, Banten. Tigaraksa 0.889 correlation of 0.889 means that there is influence between the services credit unions in improving the productivity of the small business market muddy in Banten province Tigaraksa district is strong enough and the direction (because the result is positive), the direction means that if the service is high, the savings and credit cooperatives  improving the productivity of small businesses  market in Banten province Tigaraksa district is also high. The correlation between the two variables are significant because significant numbers of 0.000 <0,05.cost number R Square (r2) of 0791 that number can be used to observe the effect of service of credit unions in improving the productivity of small businesses wet market in Banten province Tigaraksa district (determinant coefficient ). The figures are intentions that influence credit unions in the service of improving the productivity of small businesses wet market in Banten province Tigaraksa district is 99.23%and the rest is inffuence by other variable of 0,77% . Keyword: cooperative, service, credit